New Metalimnobia crane flies (Diptera, Limoniidae) from China with an update of species distributions - Ye Jiang; Xiao Zhang (ZooKeys, 2020)
Two new species of the genus Metalimnobia Matsumura, 1911 from southwest China, M. (M.) bicolor sp. nov. and M. (M.) caudifusca sp. nov., are described and illustrated. The new species can be distinguished from congeners by their wing patterns and male genitalia. New distributional data are given for the following species: M. (M.) bifasciata (Schrank, 1781), M. (M.) quadrinotata (Meigen, 1818) and M. (M.) tenua Savchenko, 1976. An updated key for all Chinese Metalimnobia crane flies is presented.